The Effect of Regional Expenditure, Balancing Funds and BPK Audit Findings on Regional Government Financial Performance - Indriani, Rima; Komala, Lenda (Santoso Academy Network, 2024)
Performance measurement is a key strategy for local governments in achieving good governance. This study examines the impact of balancing finances, regional expenditures, and Supreme Audit Agency (BPK) audit results on the financial performance of DKI Jakarta’s local government from 2010 to 2016. Secondary data was sourced from DKI Jakarta’s Regional Government Financial Reports and Budget Realization Reports, with the census method used to analyze all budget realization data during the period. Multiple linear regression was applied as the analytical technique. The results indicate that regional spending, balancing funds, and BPK audit findings significantly influence the financial performance of local governments. These findings emphasize the importance of efficient and targeted regional expenditure allocations. Additionally, local governments must address BPK audit findings with urgency to enhance governance and transparency. Utilizing financial data and audit findings as a foundation for decision-making can further strengthen financial management. Managerial implications suggest that local governments should optimize resource allocation and integrate audit results into strategic planning to improve fiscal accountability. By doing so, they can promote effective financial governance, ensuring public funds are used responsibly to achieve development goals and enhance public trust.